Evaluation of role of mean corpuscular volume and RBC-histogram in analysing anaemias as a rapid method in comparison to peripheral smear evaluation - Dr. O. Sirisha; Dr.M.N.P. Charan Paul; Dr. P. Yujwal Raj (Tropical Journal of Pathology and Microbiology, 2019)
Objective: From ages, Peripheral smear evaluation is being considered as the gold standard for evaluation of anaemias. Various other parameters have been assessed for their role as a substitute for peripheral smear. The present study evaluates Mean Corpuscular Volume (hereby referred to as MCV) and RBC-histograms if they are reliable as substitutes for the smear evaluation.Materials & Methods: This is a prospective study conducted at the department of Clinical Pathology, Bhaskar Medical College. A total of 129 cases diagnosed as having anaemia were included in the study. Initially each case was analysed based upon the cell counter values, RBC indices & RBC histogram. A detailed peripheral smear evaluation was done later for each case. The results were compared and analysed statistically. Sensitivity, Specificity and Positive, Negative predictive values were calculated.Results: Female cases outnumbered the male patients. Microcytic hypochromic anaemia was the most common type (61%); MCV was able to detect 75% of cases of macrocytic anaemia and 76% of cases of microcytic hypochromic anaemia. In contrast, 65% of cases of dimorphicanaemia had MCV values in the normal range. RBC-histograms were able to detect 63% of cases, 83% of cases with macrocytic anaemia, only 41% of patients had the characteristic double-peak on histograms.Conclusion: Though MCV and RBC histograms can detect most of the cases of macrocytic anaemia and microcytic anaemias with accuracy, a case with normal MCV and increased RDW requires a peripheral smear examination as the findings were variable in dimorphic anaemia.